Innovation in Trás-os-Montes traditional products: consumer perception on extra-long maturation goat cheese - Mendonça, Álvaro (2018)
Traditional agricultural and agri-food products are at the center of attention as instruments for enhancing agricultural and rural development. These products are seen as a central element in space planning, landscape preservation and nature conservation, and in combating depopulation of poor rural areas (Tibério et al., 2008). This research was based on data from a survey on the consumption preferences of goat cheese from Trás-os-Montes region, Portugal. The study was developed within the ProDeR Project - PA 49.481, measure 4.1 - Cooperation for Innovation - Development of “Serrana” goat cheese with extra-long maturation as a result of a partnership between a research unit and a cooperative. The objectives of the study were to identify the consumer profile, cheese consumption habits and to compare consumers' perception about the characteristics of cheeses with different maturation periods (2, 7 and 12 months). To achieve these objectives, a quantitative, analytical, cross-sectional and observational study was developed based on a sample of 155 consumers who went to a supermarket in Bragança on May 28 and 29, 2015. To collect the data, a questionnaire was used with questions about the characteristics of the consumer, the frequency of cheese consumption and the sensorial perceptions of consumers (appearance, aroma, taste, perception of fat content, hardness, and perception of content of salt) of the cheeses with different maturation periods. The three cheeses were presented to consumers in a plastic dessert plate with the cheese code inscribed on the plate next to the slice of cheese. Each slice was about 4 millimeters thick. There was also a plate with three toasts, a napkin and a glass of water. Consumers were informed that they should clean the palate between tasting each of the three cheese slices since the slices were supplied at the same time. To cleanse the palate, consumers could turn to water and/or toasts. The data treatment was carried out using SPSS 23.0 and involved the use of descriptive statistics to identify the consumers’ profile and their cheese consumption habits; and the Friedman test was used to verify if there were statistically significant differences between the three cheeses at a significance level of 1%. Consumers’ age varied between 17 and 86 years old. In average, consumers were 52.9 years old (± 15.62). The majority of consumers was male (51.6%), married (53.0%), living in households with two people (30.3%), with a net monthly household income between € 1,001 and € 3,000 (30.3%) and a cheese frequency consumption of more than once a week (86.5%) (Table 1).